The pattern of emergence of a Middle Stone Age tradition at Gademotta and Kulkuletti (Ethiopia) through convergent tool and point technologies. Issue 91 (February 2016) - Douze, Katja; Delagnes, Anne
Abstract: The Gademotta and Kulkuletti site complex, located in the central part of the Main Ethiopian Rift, is known to be one of the richest early Middle Stone Age (MSA) sequences in East Africa. The technological assessment of three main sites provides evidence of major changes in the production of convergent tools over a period from before 280 ka (thousands of years ago) to ca. 100 ka. Important diachronic changes are identified in the manufacturing process of convergent tools, by shaping or retouching of predetermined points, and in the core reduction process that produced the corresponding blanks. These are: 1) the development of specific Levallois methods for the production of points (classical Levallois point production and Nubian type 1 core reduction); and 2) the shift from uni-bifacial invasive shaping of convergent tools to localized slight retouch of predetermined points. These technological changes in convergent tool production reveal the gradual emergence of a new set of technological behaviors that can be considered specific to the MSA. While the eastern African MSA is often considered as stable over time with minimal innovation, our results provide an insight into local behavioral mechanisms that have given rise to changes in technological systems during the early MSA.